Mapping of Leading Livestock Subsector in East Java Province - Sutawi, Sutawi (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Livestock subsector contributes substantially to the economy of East Java Province. Thisstudy was conducted to identify and mapping the leading livestock subsector in 38 districts/cities inEast Java province based on data GDRB in 2009-2013. The analytical method used is LocationQuotient (LQ), Shift-Share (SS), and Klassen typology. LQ analysis results indicate that the livestocksubsector is a bases sector (LQ>1) in 26 districts/cities and the non base (LQ<1) in 12 districts/cities.SS analysis showed that the growth of the livestock subsector is progressive (SS>0) in 7districts/cities, while in 31 districts/cities is slow (SS<0). Based on analysis Klassen typology thisresearch concluded that the livestock subsector is the leading sector (LQ>1 and SS>0) in 7districts/cities, namely Bojonegoro, Madiun, Mojokerto, Pacitan, Pasuruan, Trenggalek, and Tuban.Â Key Words: Livestock Subsector, Location Quotient, Shift-Share, Klassen Tipology